Bed management considering bed-blocking and elective patient admissions using simulation optimisation. (7th May 2020) - Aghaabdellahian, Zahra; Bijari, Mehdi
Treatment process in health centres is mostly carried out in such a way that the patient is hospitalised in several parts of the wards during treatment. When patients are obliged to stay in a department until a bed becomes available in the next department, 'bed-blocking' occurs. Hospitals often suffer from the lack of proper planning and ineffective management of hospital beds and medical resources. In this research, we tackle this issue by introducing a multi-objective simulation optimisation model to determine the optimal number of elective admissions, the appropriate number of beds, and the number of patients who are forced to discharge in each ward. The model minimises hospital costs and the number of patients who are blocked. Due to the complexity of the issue, two meta-heuristic approaches are developed to solve the model. In this regard, five simulation optimisation algorithms have been implemented to solve the model and compare the results. By solving the presented algorithms, Pareto optimal frontiers are obtained in various states.